An Analysis Of Npa Management And Asset Resolution – Evidence From The Indian Banking Sector (Journal of Namibian Studies : History Politics Culture, 2023)
In the modern age of intense competition and lessened entrance barriers, banks must decide whether to survive. PSU banks in India are currently experiencing higher loss volumes together with rising Non-Performing Asset (NPA) ratios. Profit margins have therefore been squeezed as a result of the rise in provisioning for these NPA. Additionally, when the gross NPA increased relative to the gross advances, the asset quality declined. It has been mentioned that a variety of external factors have an impact on asset quality, but internal elements are equally significant; bank boards must implement risk management procedures following their risk tolerance.  The idea here is to study the Levels of Non-Performing Assets of the selected PSU banks and their asset quality (i.e. Return on Assets) and performance of the banks (i.e. Return on Equity). The asset resolution and its influence on bank's performance are analyzed through fixed effects model (FEM) and random effects model (REM) of panel data. Further to conclude by conceptually looking at the future direction of the RBI regulations for PSU banks.